Data from: Diel predator activity drives a dynamic landscape of fear ... - Kohl, Michel T.; Stahler, Daniel R.; Metz, Matthew C.; Forester, James D.; Kauffman, Matthew J.; Varley, Nathan; White, Patrick J.; Smith, Douglas W.; MacNulty, Daniel R. (Dryad, 2018)
A ‘landscape of fear’ (LOF) is a map that describes continuous spatial variation in an animal’s perception of predation risk. The relief on this map reflects, for example, places that an animal avoids to minimize risk. Although the LOF concept is a potential unifying theme in ecology that is often invoked to explain the ecological and conservation significance of fear, little is known about the daily dynamics of a LOF. Despite theory and data to the contrary, investigators often assume, implicitly or explicitly, that a LOF is a static consequence of a predator’s mere presence within an ecosystem. We tested the prediction that a LOF in a large-scale, free-living system is a highly-dynamic map with ‘peaks’ and ‘valleys’ that alternate across the diel (24-hour) cycle in response to daily lulls in predator activity. We did so with extensive data from the case study of Yellowstone elk (Cervus elaphus) and wolves (Canis lupus) that was the original basis for the LOF concept. We quantified the elk LOF, defined here ... : Kohl_etal_NorthernRangeCowElkData_2001thru2004This is GPS data collected by Dr. Mark Boyce and National Park Staff as part of the early monitoring efforts of elk following wolf reintroduction. Winter data (see paper for information) is cleaned and operational. Migration data and Summer is not. Fix intervals vary by individual so please contact Dan MacNulty at Utah State University for additional information pertaining to these schedules and any other pertinent information. These data were assembled from three different sources (Mao, Varley, Evans), so duplicated records may exists for some records.Kohl_etal_NorthernRangeElkData_2001thru2004.csvFinal Analysis Dataset for Matched-Case Control Elk Habitat SelectionFinalAnalysis_MCCDataset.csvSummary information for Historic Northern Yellowstone Elk DataKohl_etal_NorthernRangeElkData_SummaryInformation.xlsxDiel activity of wolvesWolf Diel Activity.xlsx ...